Randomized controlled trials and real-world evidence for market access and surveillance of high-risk products: the example of paclitaxel - Behrendt, Christian-Alexander; Rother, Ulrich; Rümenapf, Gerhard; Uhl, Christian; Görtz, Hartmut; Böckler, Dittmar (Gefässchirurgie, 2020)
In 2018 and 2020, two meta-analyses using summary-level data from randomized controlled trials reported worse mortality following the application of paclitaxel-coated stents and balloons in femoropopliteal and crural arteries. These results initiated a heated global discussion concerning the validity of this association, while various observational studies using clinical and administrative registries proved the safety of coated devices. This article aimed to summarize the development and adoption of paclitaxel-coated balloons and stents for the treatment of peripheral arterial occlusive disease in clinical practice, research, and practice guidelines. It especially focusses on the European Unionʼs medical device regulation, which has far-reaching implications for the market approval and monitoring of high-risk medical devices.
Online veröffentlicht: 27. November 2020
Gesehen am 14.12.2023